Validity of self‐reporting depression in the Tabari cohort study population - Mehran Zarghami; Fatemeh Taghizadeh; Mahmood Moosazadeh; Motahhareh Kheradmand; Keyvan Heydari (Neuropsychopharmacology Reports, 2020)
Abstract Aims Depression is a common cause of mortality and morbidity worldwide. To detect depression, we compared BDI‐II scoring as a valid tool with participants' self‐reporting depression. Methods The sample size was determined to include 155 participants with positive self‐reporting of depression in a total of 1300 samples with 310 healthy participants were included in the study through random selection. In order to evaluate the diagnostic value of self‐reporting, BDI‐II was completed by blind interviewing to the case group as well as to another group who reported that they were not depressed, as control. Results Sensitivity, specificity, accuracy, false positive, false negative, positive, and negative predictive values of self‐reporting were calculated 58.4%, 79.1%,73.4%, 20.8%, 41.6%, 51.8%, and 83.2% for the total population, respectively, as well as, sensitivity, specificity, accuracy, positive, and negative predictive values of self‐report in males were 83.3%, 77.2%, 77.1%, 43.8%, and 95.6% and 53.7%, 78.1%, 71.2%, 49.2%, and 81.1% for females, respectively. Conclusion The positive predictive value and sensitivity of self‐reporting are insufficient in total population and females, and therefore self‐reporting cannot detect depressed patients, but regarding to its average positive predictive value, perhaps, it can be used to identify nondepressant individuals.